PENGARUH DIMENSI KUALITAS PELAYANAN TERHADAP KEPUASAN KLAIMEN PADA PT. ASURANSI MEGA PRATAMA SEMARANG - Danang Dwi Nugroho, 12.05.51.0200 (Students Journal of Economic and Management, 2016)
This study aims to examine and analyze the dimensions of service quality to satisfaction klaimen at PT. Asuransi Mega Pratama Semarang with the perspective of marketing theory. Appropriate marketing theory that almost all companies in order to optimize the output achieved. For that you need to do is continual improvement in the areas of customer satisfaction. This approach can work well if the effort to improve the quality of service, because of the quality of service is the most important dimension in the improvement of marketing. The work done by the company to improve customer satisfaction, namely by taking into account the quality of dementia care. Research using quantitative approach. Sampling technique performed is purposive sampling technique, which is a non-probability sampling sample which conform to certain criteria. Where the sample is customers who make a claim as many as 88 people klamen. Tools data analysis using multiple linear regression, hypothesis testing using the F and t test. The research found that service quality dimension consists of physical evidence (tangibles), reliability (reliability), Responsiveness (responsiveness), assurance (assurance) and Empathy (empathy) partially or simultaneously positive and significant impact on satisfaction klaimen at PT. Asuransi Mega Pratama Semarang; dimensions of responsiveness (responsiveness) has the most impact on satisfaction klaimen at PT. Asuransi Mega Pratama Semarang; dimensions of service quality contributed to klaimen satisfaction at PT. Asuransi Mega Pratama Semarang amounted to 92%. This study has a limitation that only test klaimen satisfaction PT. Asuransi Mega Pratama Semarang. Thus the results of this study may not be completely accurate when applied to the PT. Other Insurance. Perhaps there are other variables outside the research model also influential in increasing satisfaction klaimen. Keywords: Â Â Â Tangibles, Reliability, Responsiveness, Assurance, Empathy and Customer Satisfaction